Current nanotechnology advances in diagnostic biosensors - Barbosa, Ana Isabel Ferreira (2020)
Current diagnostics present challenges that are imposed by increased life expectancy in the worldwide population. These challenges are related, not only to satisfy the need for higher performance of diagnostic tests, but also to the capacity of creating pointâ ofâ care, wearable, multiplexing and implantable diagnostic platforms that will allow early detection, continuous monitoring and treatment of health conditions in a personalized manner. These health challenges are translated into technological issues that need to be solved with multidisciplinary knowledge. Nanoscience and technology play a fundamental role in the development of miniaturized sensors that are cheap, accurate, sensitive and consume less power. At nanometre scale, these materials possess higher volumeâ toâ surface ratio and display novel properties (composition, charge, reactive sites, physical structure and potential) that are exploited for sensing purposes. These nanomaterials can therefore be integrated into diagnostic sensing platforms allowing the creation of novel technologies that tackle current health challenges. These nanomaterialâ enhanced sensors are extremely diverse, since they use numerous types of materials, nanostructures and detection modes for a multitude of biomarkers. The purpose of this review is to summarize the current stateâ ofâ theâ art of nanomaterialâ enhanced sensors, emphasizing and discussing the diagnostic challenges that are addressed by the different engineering and nanotechnology approaches. This review also aims to identify the drawbacks of nanomaterialâ enhanced sensors, as well as point out future developmental directions.